1997
DOI: 10.1073/pnas.94.8.4113
|View full text |Cite
|
Sign up to set email alerts
|

Familial multiple system tauopathy with presenile dementia: A disease with abundant neuronal and glial tau filaments

Abstract: Neurofibrillary lesions made of hyperphosphorylated microtubule-associated protein tau constitute not only one of the defining neuropathological features of Alzheimer disease but also are present in a number of other neurodegenerative diseases with dementia. Here we describe a novel autosomal dominant disease named familial ''multiple system tauopathy with presenile dementia,'' which is characterized by abundant fibrillary deposits of tau protein in both neurons and glial cells. There are no detectable deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
218
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 324 publications
(232 citation statements)
references
References 45 publications
13
218
0
1
Order By: Relevance
“…Axonal swelling, vacuolization, and axonal spheroids are also seen in Drosophila (25) and some mouse tau Tg models (10,26,27). Also, dilated axons were reported in an FTDP-17 multiple system atrophy family (3,28). Both soluble and insoluble tau is phosphorylated at some of the same sites hyperphosphorylated in AD, FTDP-17, and other tauopathies (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Axonal swelling, vacuolization, and axonal spheroids are also seen in Drosophila (25) and some mouse tau Tg models (10,26,27). Also, dilated axons were reported in an FTDP-17 multiple system atrophy family (3,28). Both soluble and insoluble tau is phosphorylated at some of the same sites hyperphosphorylated in AD, FTDP-17, and other tauopathies (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Mutation G389R also affects all six tau isoforms and the majority of filaments resemble the straight filaments of Alzheimer disease , despite the presence of Pick-like bodies by light microscopy. In contrast, in the case of mutations that increase the splicing of exon 10, the filaments appear as irregularly twisted ribbons, which are made of tau isoforms with four repeats (Spillantini et al 1997). In the case of mutation P301L in exon 10, which affects only four-repeat tau isoforms, the majority of filaments consists of narrow, irregularly twisted ribbons, with a smaller number of straight filaments (Spillantini et al 1998c).…”
Section: Implications For Understanding Alzheimer Diseasementioning
confidence: 99%
“…A subsequent immunohistochemical study demonstrated extensive similarities between the profile of immunodetectable polypeptides in LBs and Lewy neurites suggesting that both lesions result from a common pathogenic mechanism (Dickson et al, 1994). Spillantini et al, 1997a). Some well characterized`tauopathies' are: progressive supranuclear palsy, Pick's disease, corticobasal degeneration, familial frontotemporal dementia and parkinsonism linked to chromosome 17 (FTDP-17) and Guam amyotrophic lateral sclerosis/parkinsonism dementia complex.…”
mentioning
confidence: 99%